Latin America's democratic crusade : the transnational struggle against dictatorship, 1920s-1960s - Wells, Allen, 1951- (Yale University Press, 2023)
By emphasizing Latin American reformers' decades-long struggle to defeat authoritarianism, this transnational history challenges the timeworn Cold War paradigm and recasts the region's political evolution Scholars persist in framing the Cold War as a battle between left and right, one in which the Global South is cast as either witting or unwitting proxies of Washington and Moscow. What if the era is told from the perspective of the many who preferred reform to revolution? Scholars have routinely neglected, dismissed, or caricatured moderate politicians. In this book, Allen Wells argues that until the Cuban Revolution, the struggle was not between capitalism and communism-that was Washington's abiding preoccupation-but between democracy and dictatorship. Beginning in the 1920s, the fight against authoritarianism was contested on multiple fronts-political, ideological, and cultural-taking on the dimensions of a political crusade. Convinced that despots represented an existential threat, reformers declared that no civilian government was safe until the cancer of dictatorship was excised from the hemisphere. Dictators retaliated, often with deadly results, exporting strategies that had been honed at home to guarantee their political survival. Grafted onto this war without borders was a belated Cold War, with all its political convulsions, the aftershocks of which are still felt today.
Keywords: Latin America -- Politics and government -- 20th century.; Democracy -- Latin America -- History -- 20th century.; Dictatorship -- Latin America -- History -- 20th century.; Latin America -- Foreign relations -- United States.; United States -- Foreign relations -- Latin America.; Latin America -- Foreign relations -- 20th century.; United States -- Foreign relations -- 20th century.; Amérique latine -- Politique et gouvernement -- 1948-1980.; Autoritarisme -- Amérique latine.; HISTORY / Latin America / General.; Democracy.; Dictatorship.; Diplomatic relations.; Politics and government.; Latin America.; United States.; 1900-1999; History.